Avaliação comparativa de fungicidas e antibióticos no controle de Alternaria spp em couve-flor - Carrijo , Iêdo Valentim; Alves Pereira, Antônio; Pereira , Welington; Martins Chaves , Geraldo; Ferreira da Silva, Roberto (Revista Ceres, 2025)
Nine fungicides and three antibiotics were tested under greenhouse conditions for control of Alternaria spp. in cauliflower (Brassica oleracea var. botrytis). Of these, five products (Piomay, Manzate, Cuprosan, Kasumin, and Daconil) were tested under field conditions. Piomay proved the most efficient product, showing the highest yield, lowest index of silique infection, highest rate of seed germination, and the lowest percentagem of fungus-infected seeds.